Effects of biodiesel from used frying palm oil on the exhaust emissions of an indirect injection (IDI) diesel engine - SAYIN, CENK (AMER CHEMICAL SOC, 2008)
In our previous paper, the influences of biodiesel and its blends on the performance, combustion, and injection characteristics of an indirect injection (IDI) diesel engine have been discussed. The results have indicated that, when the test engine was fueled with biodiesel and its blends, the maximum brake torque, brake thermal efficiency, and brake power dropped, while the brake-specific fuel consumption increased compared to the petroleum-based diesel fuel (PBDF). The main differences in the combustion and injection characteristics of biodiesel and its blends are earlier premixed combustion, shorter ignition delay, higher cylinder gas pressure, and earlier start of injection in terms of the PBDF. This paper discusses the exhaust emission results obtained in the same study. The emission results showed that carbon monoxide (CO), unburned hydrocarbon (HC) emissions, and smoke opacity decreased with the increase of biodiesel percentage in the fuel blend for all engine speeds under the full-load condition. However, NOx and CO2 emissions showed different behaviors in terms of the engine speed.
Keywords: FUEL; PERFORMANCE; COMBUSTION; ESTER; TESTS